Improved placental vascular repair in a rat preeclampsia model by implantation of endothelial progenitor cells treated with platelet microparticles - Zhenya Fang; Anna Li; Yaqiong Sun; Xietong Wang; Meihua Zhang (Taylor & Francis Group, 2020)
Objective: To detect the role of endothelial progenitor cells (EPCs) treated with platelet microparticles (PMPs) in preeclampsia. Methods: EPCs treated with/without PMPs were labeled and injected to PE rats. The differentiation of EPCs, the change of endothelial nitric oxide synthase (eNOS), blood pressure and proteinuria were measured. The blood pressure and proteinuria increased in each of PE groups, and were improved by EPCs which was strengthened by PMPs. Transplantation of EPCs increased placental angiogenesis. The trend of change of NO was the same as blood pressure. Conclusion: Transplantation of EPCs treated with PMPs improved blood pressure and proteinuria more effectively.